RAPPORTI SOCIALI E LOCUZIONI RIGUARDANTI LE PARTI DEL CORPO IN VIETNAMITA E IN ITALIANO: UN APPROCCIO CONTRASTIVO SEMANTICO NELLA PROSPETTIVA DELL’EMBODIMENT (Journal of Foreign Language Studies, 2023)
Both Vietnamese and Italian refer to abstract concepts denoted from concrete identifiers as conceptual metaphor - a term proposed by Lakoff and Johnson (2005). This study examines the meanings of both Vietnamese and Italian fixed expressions comprising words of body parts yet denoting social relations and abstract notions. From a cognitive-linguistic perspective, it investigates cognitive characteristics of the Vietnamese and Italian when they foster expressive values of new concepts. Also, the embodiment theory is used to explain the basis for forming a new semantic content from original meanings. The research results provide an overview of the meanings of these fixed expressions, thereby revealing Vietnamese and Italian cultures and thinking.
Keywords: semantic; vocabulary of body parts; Vietnamese; Italian; embodiment